PEMBERDAYAAN PEREKONOMIAN UNTUK MEMBANGUN INOVASI MASYARAKAT YANG KREATIF PADA MASA PANDEMI COVID 19 DENGAN PELATIHAN PEMBUATAN KESET DI DESA PONDOK JAGUNG TIMUR - Agus Sriyanto; Yugi setyarko; Elizabeth; Rina Ayu Vildayanti (Pusat Riset dan Inovasi Nasional, 2022)
The problem faced by housewives in Pondok Jagung Timur Village, North Serpong, South Tangerang is that they do not understand how the handicraft business produced can meet the needs and desires of consumers and can be sold and reach the hands of consumers and is widely liked and known by consumers. Due to this lack of understanding and knowledge, people lose business opportunities, especially housewives. Community service programs in the form of training on mat making to build creative community innovations during the COVID-19 pandemic. to improve the social welfare of its members and provide benefits to the surrounding community, especially in developing countries such as Indonesia.